Effect of Pot Size on Growth, Flowering and Pot Presentability of Azalea Cultivars - Thapa, Suman; Dilta, B.S.; Gupta, Y.C.; Bhardwaj, S. K.; Gupta, R. K.; Negi, Narender (International Journal of Bio-resource and Stress Management, 2015)
The present investigation was carried out at the experimental farm of DYSPUH&F, Nauni, Solan (H.P) during 2012-13 to find out the most suitable cultivar and pot size for producing the best quality and most presentable potted azaleas and laid out in CRD (factorial) with 45 treatment combinations of fifteen cultivars and three pot sizes replicated thrice with five pots treatment-1. Fifteen cultivars viz., ‘John Herrens’, ‘Winter Hawk’, ‘White Rosebud’, ‘Boy-O-Boy’, ‘Summer Time’, ‘Pink Tama’, ‘Red Tomahawk’, ‘Shanghai Baby’, ‘Super Red’, ‘Nightingale’, ‘Empress’, ‘White Bouquet’, ‘Lady Love’, ‘Anniversary Joy’ and ‘Royalty’ and three pot sizes i.e. 25 cm, 20 cm and 15 cm diameter pots, respectively were tested. The cv. ‘White Bouquet’ recorded maximum no. of shoots plant-1, plant spread, no. of flowers plant-1, no. of flowers plant-1 open at a time, duration of flowering and pot presentability score. However, the maximum values for plant height and shoot length were recorded in ‘Royalty’; ‘Empress’ took maximum time for flower bud formation as well as flowering and ‘Pink Tama’ produced largest flowers. In regard to the effect of pot sizes, 25 cm diameter pots exhibited maximum plant height, maximum shoots plant-1, shoot length, plant spread, days for flower bud formation, time taken for flowering, no. of flowers plant-1, flower diameter, no. of flowers open at a time, duration of flowering and pot presentability score.